Comparison Study between Face Shield and Pocket Mask for Adult Basic Life Support Training for Health Care Provider - Boonmak, Polpun; Boonmak, Suhattaya; Mitsungnern, Thaponawong; Chareonpol, Fa-ngam (Srinagarind Medical Journal, 2014)
Background and objective: Basic life support (BLS) is essential for health care providers. Face shield and pocket mask were used for mouth to mouth ventilation. Both equipments differ in ease to use and its cost. This study was aimed to compare between pocket mask and face shield for mouth to mouth ventilation training in basic life support course for health care providers (HCP). Methods: This study was prospective randomized controlled trial. We studied in students who attended adult BLS course for HCP at Khon Kaen University Simulation Center, Faculty of Medicine, Khon Kaen University. It was a three hours course for knowledge and skill teaching. During mouth to mouth ventilation training, Students were divided into two groups. Group practiced with face shield and another group with pocket mask. Students practiced with equipments until they performed successful ventilation. If they showed unsuccessful ventilation, Instructors repeatedly trained them until obtainingthe skill. Then they trained chest compression until had appropriated skill. After the training, we evaluated their ventilation skill when performed with chest compression. Then all students were trained with the standard BLS course. Results: We included 76 students into the study. Successful ventilation in first attempt with face shield group and pocket mask group were 16.8 % and 68.4 %, respectively (p = 0.001). Mean (SD) of number of attempt to first successful ventilation with face shield group and pocket mask group were 2.24 (1.09) and 1.34 (0.59), respectively (p < 0.0001). Mean difference was 0.87 (95%CI 0.47-1.27). Mean (SD) of number of attempt to first successful ventilation combined with chest compression with face shield group and pocket mask group were 1.29 (0.66) and 1.58 (0.92), respectively (p = 0.12). Conclusion: Pocket mask for mouth to month ventilation was easier than face shield ventilation training. However, after successful training, both equipments could be used with chest compression without compromise. This data may be useful for BLS for HCP training.